Role of Manpower of Prisoners of Nazi Concentration Camps in the Third Reich Economy - Piper, Franciszek (Studia Historiae Oeconomicae, 1979)
This article analyzes the role of concentration camp inmates as a labor force in the Nazi German war economy during World War II. Following the failure of the Blitzkrieg in 1942, Germany faced a growing labor shortage. In response, the regime increasingly relied on foreign laborers and prisoners of war, but these measures were not sufficient to cover the deficit. The study focuses on the underutilized potential of concentration camp prisoners in addressing this manpower gap.The aim of the study is to examine why, despite growing labor demands, concentration camp inmates played only a limited role in Nazi economic plans. Drawing on historical literature, official wartime documents, and postwar tribunal records, the article investigates the ideological, organizational, and logistical barriers to the full employment of camp prisoners. Initially, Heinrich Himmler restricted the use of prisoners to SS-controlled enterprises, prioritizing the concentration camps’ original functions: extermination, punishment, and terror. Most prisoners in 1942–43 worked in agriculture, quarries, or remained idle, despite rising industrial needs. Only after the Stalingrad defeat in 1943 did policy shift toward broader employment of inmates in private industry and armament factories, as reflected in the rapid growth of subcamps. By late 1944, approximately 500,000 prisoners were working in the German economy, with up to 250,000 in private industry. However, even at its peak, prisoners accounted for only 1–1.5% of Germany’s total workforce. Harsh treatment, starvation, and high mortality (e.g., 110,000 deaths in one year) severely limited their economic productivity. The study concludes that Nazi ideology – favoring extermination and terror over rational labor use – ultimately prevented the efficient deployment of camp inmates. As such, concentration camps are remembered not as centers of labor contribution but as symbols of unprecedented human atrocity.